Influenza B-induced Lymphopaenia: A Brief Mechanistic Review - Syed Ibrahim Jamallulail (Asian Journal of Medicine & Health Sciences, 2023)
Influenza is a common respiratory viral infection which is prevalent world-wide. Significant human infections are generally caused by the influenza A and B virus. Influenza often causes an abrupt onset-illness with high fever, constitutional and respiratory symptoms commonly known as ‘flu’. Reactive lymphocytosis is the hallmark of most viral infections. However, influenza is commonly observed to present with an early transient lymphopaenia which may be profound. We present a case of a 20-year-old student diagnosed with symptomatic influenza B who presented with a lymphocyte count of 0.6 x 109/L within 24 hours of symptom onset. This article aims to review the current understanding into the mechanisms underlying lymphopaenia development in influenza. Evidence from experimental and human studies are collated and discussed.